How Myanmar Is Working to Maintain Essential Services for People Living With HIV and Key Populations During the Covid-19 Pandemic - Oo Htun Nyunt MBBS, MPH; Nanda Myo Aung Wan MBBS; Pyae Soan MBBS, MPH, PDoc; Oussama Tawil BA, MA; Myo Kyaw Lwin MBBS, MPP; May Thu Aung Hsan MBBS, MPH; Khin Mar Win; Fabio Mesquita MD, PhD (Journal of the International Association of Providers of AIDS Care, 2021)
Background: Maintaining essential HIV services has being a Global challenge during the COVID-19 crises. Myanmar has 54 million inhabitants. Neighbor of China, Thailand, India and Bangladesh it was impacted by COVID-19, but came up with a comprehensive and effective response, following WHO recommendations. The HIV Prevalence is 0.58% and it is concentrated among key population. A HIV Contingency Plan was developed to face this challenge. Methodology: The programme-based cross-sectional descriptive study with analysis of routinely collected data from MoHS data system, between 2019 and 2020 was conducted, comparing first six months of 2019 and 2020. Results: HIV outreach activities and HIV testing were slightly affected after detection of first COVID-19 case, till mid May 2020. After that, outreach activities resumed. Introduction of HIV self-testing was initiated. 72% of more than 21,000 PWID on MMT were receiving take home dose up to 14 days and 60% of ART patients were receiving 6 months ARV dispensing. Conclusion: Essential HIV services were maintained.